Density Functional Theory Study of Electronic Structure and Optical Properties of Ln3+-Doped γ-Bi2MoO6 (Ln=Gd, Ho, Yb) - Bohang Zhang; Gaihui Liu; Huihui Shi; Qiao Wu; Suqin Xue; Tingting Shao; Fuchun Zhang; Xinghui Liu (Crystals, 2023)
Based on density functional theory (DFT), theoretical models of three kinds of lanthanide rare earth metal ion-doped γ-Bi2MoO6 were constructed (Ln-BMO (Ln=Gd, Ho, Yb)). The geometric structure, electronic structure, and optical properties of the model were calculated, and the influence of doped Ln3+ ions on the structures and properties of the system was analyzed. The results revealed that the substitution of smaller ionic radius Ln3+ ions for Bi3+ ions caused a contraction of the lattice parameters. At the same time, the contribution of the [Ln]4d near valence band and conduction band reduced the bandwidth of γ-Bi2MoO6, forming the Ln-O ionic bond with different strengths to obtain higher charge conductivity and charge-separation ability. Secondly, Ln3+ ions have a strongly ionic charge, which leads to the appearance of optical absorption bands in the infrared region and part of the visible region. This reduces the reflection in the visible region, improves the utilization rate, delays the loss of electron energy, and promotes phase matching in the visible region. And the Gd3+-doped system has better photocatalytic activity than the other Ln3+-doped system. This research provides theoretical insights into doped lanthanide rare earth ions and also provides strategies for the modification of γ-Bi2MoO6 nanomaterials.